An analysis of aerobic resistance and metabolic capacity of indoor soccer players from 62th Battalion of Joinville Infantry - Gasparete, Luiz Fernando; Werlang Coelho, Carla; Poffo, Helena; Fleischmann, Eriberto (O Mundo da Saúde, 2007)
The aim of this study was to analyze the aerobic resistance and the metabolic capacity of indoor soccer players of Joinville infantry 62º battalion aiming at training prescriptions. The sample was composed by 12 athletes, with ages 30.4±4.9anos, weight 71.8±7.1kg and height 170.1±0,1cm. After pre-evaluations carried through in the Laboratory of Exercise Physiology (LAFIEX), a test of effort in mat (Bruce) was carried through that was considered finished at the moment the athlete reached its maximum state of exhaustion. Blood lactate (BL) was measured through a blood sample obtained in the earlobe (lactometer 1500 YSI SPORT) at the end of each period of training and after three and five minutes of recovery. Cardiac frequency (CF) was measured at every minute of the test and after three and five minutes of recovery (frequencimeter - Polar). Results indicate that the anaerobic threshold of most subjects was reached around the 4th period of training of the protocol (4.86±2.3 mMol/l) at an average CF of 156±20.9 bpm. In the recovery phase, the results of BL and CF in minute 3 and 5 had been respectively: 11.04 bpm 2.3 mMol/l and 122±14.6 bpm; e 10.44±2.0 mMol/l and 118±15.7 bpm. In data analysis it was observed that only 41.7% had finished the 8th period of training, an indication that attaining the goals of the modality an individualized training is necessary using as reference the results of the said pre-test. We conclude that the athletes obtained a result above the expected one for the phase they are presently in, being able for doing physical training